Influence of the intestinal microbiota on parkinson's disease. Review - Maldonado Gómez, Alejandra Belen (2023)
The aim of the present study is to analyze the role of the gut microbiota in the progression of Parkinson's disease by performing a literature review. Parkinson's disease is a neurodegenerative disease caused by the degeneration of dopaminergic neurons in the substantia nigra (pars compacta). The frequency of the disease varies with age and gender, being more common in men over 60 years of age. The main cause of neuronal death is unknown and may be related to degenerative processes such as mitochondrial dysfunction, a-synuclein aggregation, altered autophagy, endoplasmic reticulum (ER) stress or dysregulation of intracellular calcium homeostasis. The gut microbiota is an integral part of the human organism and contributes to many physiological processes, including immune defense. The interaction between the gut microbiota and the central nervous system (CNS) is known as the microbiota-gut-brain axis (MIC). Gut dysbiosis, an alteration in the composition and function of the gut microbiota, has been found in people with Parkinsons disease. In addition, it has been shown that some compounds produced by the gut microbiota may have antiinflammatory and antioxidant properties that could be benefcial in this disease. A link has also been found between the gut microbiota and the production of dopamine, a key neurotransmitter that is decreased in people with Parkinsons disease.